Society and economy in North-East India - Momin, Mignonette; Mawlong, Cecile A. (New Delhi : Regency Publications, 2004)
Contributed papers presented at a symposium held in 1999.
Gifted by Prof. Kapil Kumar, IGNOU
Keywords: Economic history; India, Northeastern -- Social conditions -- Congresses; India, Northeastern -- Economic conditions -- Congresses